Effects of FGFR inhibitors TKI258, BGJ398 and AZD4547 on breast cancer cells in 2D, 3D and tissue explant cultures - Kähkönen TE; Toriseva M; Petruk N; Virta AR; Maher A; Eigeliene N; Kaivola J; Boström P; Koskivuo I; Nees M; Tuomela JM; Ivaska KK; et al. (SPRINGER, 2022)
Purpose
Fibroblast growth factor receptors (FGFR) and pathways are important players in breast cancer (BC) development. They are commonly altered, and BCs exhibiting FGFR gene amplification are currently being studied for drug development. Here, we aimed to compare the effects of three FGFR inhibitors (FGFRis), i.e., non-selective TKI258 and selective BGJ398 and AZD4547, on different BC-derived cell lines (BCCs) and primary tissues.
Methods
The human BCCs MCF-7 and MDA-MB-231(SA) (wild-type FGFR) and MFM223 (amplified FGFR1 and FGFR2) were analyzed for FGFR expression using qRT-PCR, and the effects of FGFRis on FGFR signaling by Western blotting. The effects of FGFRis on proliferation, viability, migration and invasion of BCCs were assessed in 2D cultures using live-cell imaging, and in 3D cultures using phenotypic analysis of organoids. To study radio-sensitization, FGFRi treatment was combined with irradiation. Patient-derived BC samples were treated with FGFRis in explant cultures and immunostained for Ki67 and cleaved caspase 3.
Results
We found that all FGFRis tested decreased the growth and viability of BC cells in 2D and 3D cultures. BGJ398 and AZD4547 were found to be potent at low concentrations in FGFR-amplified MFM233 cells, whereas higher concentrations were required in non-amplified MCF7 and MDA-MB-231(SA) cells. TKI258 inhibited the migration and invasion, whereas BGJ398 and AZD4547 only inhibited the invasion of MDA-MB-231(SA) cells. FGFRi treatment of MCF7 and MFM223 cells enhanced the inhibitory effect of radiotherapy, but this effect was not observed in MDA-MB-231(SA) cells. FGFRi-treated primary BC explants with moderate FGFR levels showed a tendency towards decreased proliferation and increased apoptosis.
Conclusions
Our results indicate that, besides targeting FGFR-amplified BCs with selective FGFRis, also BCs without FGFR amplification/activation may benefit from FGFRi-treatment. Combination with other treatment modalities, such as radiotherapy, may allow the use of FGFRis at relatively low concentrations and, thereby, contribute to better BC treatment outcomes.